A REVERSIBLE ENCEPHALOPATHY WITH ATAXIA AND UNUSUAL MRI ABNORMALITIES. Issue 11 (9th October 2013) - Panicker, Jay; Iniesta, Ivan; Wilson, Martin
Abstract : Introduction: Methyl Iodide is well recognised as an industrial toxin and accidental exposure at workplace can cause neuropsychiatric symptoms. 1 We report two cases with similar clinical presentations, and previously unreported MRI abnormalities. Case 1: A 44 year old gentleman developed visual hallucinations on his first day back from work at a pharmaceutical factory. Later he became extremely agitated and psychotic with paranoid delusions and auditory hallucinations and also developed difficulty walking. A history of possible inhalation of a gas was obtained from a colleague at workplace. Examination on admission showed nystagmus, cerebellar ataxia, asterixis and marked confusion. An MRI scan done few days after admission showed subtle signal change in the posterior fossa and CSF examination was normal. Routine bloods were normal, but Blood and urine Iodine levels were more than 100 times above the normal range. His symptoms gradually settled on observation and a small dose of antipsychotic over three weeks, though he has been left with mild behavioural changes. Case 2: A 40 year old man reported accidentally inhaling Methyl Iodide at workplace and developed walking difficulties, visual hallucinations and repeated seizures over the next 12 hours. He was admitted in status epilepticus to the local hospital and was had to be sedated and intubated as his seizures remained uncontrolled with intravenous bolus doses of Phenytoin and Sodium Valproate. Examination after weaning off sedation showed marked dysarthria, cerebellar ataxia and he also reported delusional ideas and olfactory hallucinations. MRI scans showed diffuse white matter abnormalities in the posterior fossa involving brainstem and cerebellum (similar to case 1) and routine blood and CSF investigations were normal, but blood and urine Iodine levels were more than 500 times the normal range. His symptoms gradually improved and was discharged home 8 weeks after his initial presentation, but on follow up two months later, he still needed crutches to mobilise and had persistent olfactory hallucinations. Discussion: Though Neuropsychiatric features are well recognised in Methyl Iodide toxicity in the past, abnormalities on brain imaging have not been previously reported. Both of our cases presented a distinct clinical and radiological picture with encephalopathy, ataxia and neuropsychiatric symptoms, with similar changes in the posterior fossa on MRI. Case 2 had a more severe clinical presentation and more significant scan changes and this is possibly because he had a more severe exposure as evidenced by the higher levels of Iodine in blood and urine. Conclusion: Methyl Iodide poisoning should be considered in the appropriate clinical setting when patients present with encephalopathy, ataxia and abnormalities in the posterior fossa which can sometimes be mistaken for acute demyelination. Obtaining history of exposure is the key to the diagnosis and avoiding unecessary investigations, emphasising the importance of occupational history in these cases.